Sistem Pendeteksi Suhu Tubuh Jarak Jauh dengan MLX 90614dan NodeMCU untuk Mencegah Penularan Covid-19 Berbasis IoT - Dani Sasmoko; Iman Saufik; Nur Afifah (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
The health protocol has being an obligation in line with the implementation of Face-to-Face Learning in the school environment. Currently, the medical procedures are carried out by using a thermogun which able to detect human body temperature. The use of a thermogun is carried out by detecting the body temperature of students or visitors who entered the school environment. The used of the MLX 90614 Sensor and NodeMCU with the support of android technology, the temperature detection process can be carried out remotely based on the Internet of things. After several experiments, it was found that if the distance is more than 5cm, the temperature will not appear and the buzzer will sound two times. If the distance was less than 5cm the buzzer sounds one time and temperature data is obtained. The results will appear on the android screen, showed the temperature conditions and its distance. When the temperature exceeds 37.50C, the buzzer will sound two times and display a warning sign on Android that indicates the data at high temperatures (hot). During the experiment, there were network problems in the RTO state, so the data did not appear. RTO is a condition where data is not sent because there are obstacles in the internet network. In this research, it can be concluded that remote temperature monitoring with IOT can be done and is recommended because it will protect officers from the covid virus attack. For further research, it is recommended to add a face detector so that those with an indication of fever will have their faces photographed.